2013
DOI: 10.1136/thoraxjnl-2013-204247
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia in low and middle income countries: progress and challenges

Abstract: Pneumonia remains the leading cause of childhood mortality and the most common reason for adult hospitalisation in low and middle income countries, despite advances in preventative and management strategies. In the last decade, pneumonia mortality in children has fallen to approximately 1.3 million cases in 2011, with most deaths occurring in low income countries. Important recent advances include more widespread implementation of protein-polysaccharide conjugate vaccines against Haemophilus influenzae type B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 55 publications
4
97
0
2
Order By: Relevance
“…Africa (30%) and Southeast Asia (39%) were regions in the world with the highest incidence and severity of pneumonia cases (Zar et al, 2013). Basic Health Survey (RISKESDAS) conducted by Ministry of Health Indonesia reported that pneumonia prevalence among children under-five was 2.13% in 2007 and 1.…”
mentioning
confidence: 99%
“…Africa (30%) and Southeast Asia (39%) were regions in the world with the highest incidence and severity of pneumonia cases (Zar et al, 2013). Basic Health Survey (RISKESDAS) conducted by Ministry of Health Indonesia reported that pneumonia prevalence among children under-five was 2.13% in 2007 and 1.…”
mentioning
confidence: 99%
“…26 In Canada, viruses accounted for 64% of acute respiratory illness in HIV-infected adult outpatients, with HMPV the second most isolated pathogen, highlighting the potential importance of this pathogen in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…2 Dua juta anak berusia kurang dari lima tahun meninggal karena pneumonia per tahunnya, terutama di daerah Afrika dan Asia Tenggara. 3 Data Riskesdas menunjukkan peningkatan persentasi prevalensi pneumonia pada semua umur dari 2,1% pada tahun 2007 menjadi 2,7% pada tahun 2013.…”
Section: Pendahuluanunclassified